Pengaruh Model Pembelajaran Teams Games Tournament (TGT) dengan Permainan Boy-Boyan terhadap Hasil Belajar Bahasa Inggris Siswa Kelas I SDN Rang Perang Laok - Wirdatinnisa', Murnia; Fauziah, Humairah (Yayasan Arrahman Nahdlatul Wathan, 2024)
This research aims to determine the effect of using the Teams Games Tournament (TGT) learning model with boy-boyan games in improving the English learning outcomes of class I students at SDN Rang Perang Laok. This research is quantitative research with the type of research used as Quasi-Experimental Design, Nonequivalent Control Group Design type. Sampling used the Cluster Sampling technique with a population of 34 students consisting of classes IA and IB. Data was collected using observation, interviews, and tests. Trials on test instruments use validity tests, reliability tests, level of difficulty of questions, and distinguishing power. The data analysis used was a prerequisite test using the normality test, homogeneity test, and hypothesis testing using Mann-Whitney. Data collection was carried out through pretest and posttest, as well as learning implementation. Researchers used the Mann-Whitney hypothesis test because in the normality test, the data was not normally distributed, which shows that there is an influence of the Teams Games Tournament (TGT) learning model in improving students' English learning outcomes. The results of the data analysis showed that Asymp.Sig(2-tailed) was 0.000 with a significance level of <0.05. Based on these results, Ho was rejected and Ha was accepted. So it is concluded that there is an influence of the Teams Games Tournament (TGT) learning model with boy-boy games on English learning outcomes at SDN Rang Perang Laok as well as increasing students' activeness, courage, and self-confidence in the learning process.